2008
DOI: 10.1530/rep-07-0426
|View full text |Cite
|
Sign up to set email alerts
|

Biological interpretations of transcriptomic profiles in mammalian oocytes and embryos

Abstract: The characterization of gene-expression profiles in oocytes and embryos is critical to understand the influence of genetic and environmental factors on preimplantation and fetal development. Numerous gene-expression microarray studies using different platforms and species are offering insights into the biological processes extensively represented among the genes exhibiting differential expression. Major advances on understanding the direct relationship between gene expression and developmental competence are b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 73 publications
0
11
0
2
Order By: Relevance
“…The gene expression across critical developmental transitions is highly dynamic and has been shown to have long-term impacts on the normal development in mammalian and fish species [2529]. In particular, the embryo-to-larval stage is a crucial period in the life of marine fish [30].…”
Section: Discussionmentioning
confidence: 99%
“…The gene expression across critical developmental transitions is highly dynamic and has been shown to have long-term impacts on the normal development in mammalian and fish species [2529]. In particular, the embryo-to-larval stage is a crucial period in the life of marine fish [30].…”
Section: Discussionmentioning
confidence: 99%
“…However, IVC with FCS specifically affects important growth factors and cytokines (Pdgfa,Tdgf1,Ghr,Eps8,Mitf,Dusp6,Col4a1,Socs3,Cish), that have been shown to promote blastocyst formation and increases the rate of development in mouse, cow and rat (Hardy & Spanos 2002). Interestingly, three of these genes have been differentially expressed in somatic cell nuclear transfer (Rodriguez-Zas et al 2008). Moreover, it has been reported that some growth factors may be epigenetic regulators of embryo development (Warburton et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…By adopting a transcript counting methodology (Anders and Huber, 2010) developed for efficient and cost-effective high-throughput analysis, we will be able to detect differential expression of known protein-coding genes, non-coding RNAs (ncRNAs) and newly identified transcripts compared with sibling controls (Airik et al, 2005; Rodriguez-Zas et al, 2008; Tsutsumi et al, 2008). Bioinformatic analysis could then be used to identify candidate pathways and downstream targets that might be affected (Lu et al, 2009).…”
Section: The Value Of Systematic Transcriptomicsmentioning
confidence: 99%